Processing of polyethylene in the beam-plasma generated by a ribbon electron beam at forevacuum pressure range. (February 2022) - Klimov, A.S.; Bakeev, I. Yu; Oks, E.M.; Tran, V.T.; Zenin, A.A.
Abstract: We present research results of the surface modification of polyethylene film by plasma produced by the ribbon electron beam formed by a forevacuum-pressure plasma-cathode electron source. The electron beam was of energy 3 keV and current 150 mA. The gaseous environment was argon at a pressure of 10 Pa. The argon plasma so formed in the electron beam vicinity and at the location of the polyethylene samples was of density about 3 x 10 15 m −3 . Both direct plasma bombardment, and also energetic ion bombardment with ions accelerated to the sample from the e-beam produced plasma, were investigated. We show that this plasma or ion treatment imparts improved hydrophilic properties to the film and decreased light transmittance in the ultraviolet region. Highlights: The use of an electron beam for plasma generation provides a more convenient control of the parameters of the beam plasma. The contact angle with water decreased from a pre-treatment value of 85°–90° to as low as 10°–20° immediately following plasma/ion treatment, slowly rising over a period of weeks to around 50°–60°.